FEMINISTIC THOUGHTS IN THE 20TH AND 21ST CENTURY LITERARY WORKS OF AMERICAN FEMALE WRITERS - Meyliyeva Shafoat Erali qizi (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
One of most arguable and observable social phenomena is gender inequality which is based on feminism thoughts. Considering how literature may portray human’s life along with its values, this study is purposed to elaborate and compare how feminism thoughts and gender inequality take place in various literary works of American women from the end of 20th and 21st centuries. This study took two literary works, namely science-fiction, prose (short-story). Feminism approach as sociological approach was applied in this study altogether with comparative criticism and content analysis method. This study discussed how feminism thoughts got more supports and encouragement as the century progressed. By comparing literary works from 20th and 21st century, several important findings can be drawn, namely feminism thoughts are getting stronger along with the progression of years, both feminism and gender-inequality live through human’s values and repetitive actions, personal and family values are crucial in order to develop feminism thoughts and gender-inequality in an individual, and the change of values, especially social and cultural values can bring changes in both feminism and gender inequality phenomena.